(untitled) (Experimental biology, 2020)
Currently, the study of the structure and composition of plants is very important for medicine, perfumery, farms, etc. The section of the Asteraceae family includes Seriphidium heptapotamicum (Poljak) Ling & Y.R. Ling. This study discusses biochemical and anatomical features. According to new observations, the the previous description of the species was added by the additional information. Anatomical studies were carried out by the vegetative organs of S.heptapotamicum using the paraffin method. The anatomy of S.heptapotamicum have not been studied. Anatomically, the root cross section has the epidermis as a protective tissue in the outer layer and the endodermis is not clearly seen. The stems have a thick, well-developed layer of sclerenchyma. Leaves are equilateral. For a biochemical study, the essential oil was isolated from the aerial parts of S.heptapotamicum using a Clevenger type apparatus. The yield of S.heptapotamicum essential oil was found to be 2.4 %. The chemical composition of the essential oil was analyzed by GC-FID and GC-MS simultaneously. The chemical composition of essential oil depends on the collectionsites. The essential oil is composed of 14 components, in which the major dominant constituents were Thujone-41.10%, 1,8-Cineole-22.84%, β-Thujone-17.45% and Camphor (11.99%). In addition, the essential oil contents of S. heptapotamica have been obtained in this study. Keywords: Seriphidium heptapotamicum, Altyn-Emel, Essential Oil, GC; GC-MS.